The Meaning of the Word Al Mishbah in the Qur’an with Toshihiko Izutsu Semantic Analysis - Dini Rona Ayuni; Kharis Nugroho; Andri Nirwana AN (al-Afkar, Journal For Islamic Studies, 2024)
This study examines the meaning of the term "Al-Mishbah" in the Qur'an through a semantic analysis conducted by Toshihiko Izutsu. The term "Al-Mishbah," which literally means "lamp" or "light," has profound implications in both spiritual and moral contexts. In this research, the author explores how "Al-Mishbah" functions as a symbol of divine illumination that provides guidance to humanity. Using Izutsu's semantic approach, this article identifies the connections between "Al-Mishbah" and other concepts in Islamic thought, such as "nur" (light) and "iman" (faith), while highlighting the importance of the pursuit of truth and moral integrity in daily life. The purpose of this research is to explore the various dimensions of the meaning of "Al-Mishbah" within the context of the Islamic worldview and how this term serves as a symbol of divine guidance for humanity. The research method employed in this study is qualitative analysis with a semantic approach, encompassing the study of Qur'anic texts, interpretations of Hadith, and literature related to Toshihiko Izutsu's thought. The author also examines the relationship of "Al-Mishbah" with other concepts in Islamic thought, such as "nur" (light) and "iman." Through this analysis, the article demonstrates that understanding "Al-Mishbah" not only enriches the interpretation of the Arabic language but also deepens the insight into how divine light can guide individuals in their spiritual journeys, as well as foster collective awareness within the community.